LEGAL CERTAINTY OF ELECTRONIC CERTIFICATES IN PREVENTING LAND DISPUTES IN INDONESIA - Gloria Gita Putri Ginting; Etty Sri Wahyuni (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to analyze the legal certainty of electronic certificates as an instrument for protecting land rights and to examine their role in preventing land disputes in Indonesia. The development of digitalization of land administration through the implementation of electronic certificates is expected to improve data security, accelerate services, and minimize the risk of forgery, overlapping ownership, and administrative errors, which have been the main causes of land disputes. This study uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach. Data were obtained through a literature review of laws and regulations, court decisions, and various scientific literature related to land law and the transformation of digital-based land services. The results show that electronic certificates have the same legal force as conventional certificates as long as they are issued in accordance with applicable laws and regulations. The electronic system also guarantees data authentication, integrity, and security, thereby strengthening legal certainty for land rights holders. However, the effectiveness of electronic certificates in preventing land disputes is still influenced by the readiness of technological infrastructure, the quality of land data validation, the competence of human resources, and the level of public trust in the digital system. Therefore, strengthening regulations, improving cybersecurity, and continuously updating land databases are important factors in realizing legal certainty and reducing the potential for land disputes in Indonesia.